The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1074/jbc.c300482200
|View full text |Cite
|
Sign up to set email alerts
|

Centaurin-α1 Is an in Vivo Phosphatidylinositol 3,4,5-Trisphosphate-dependent GTPase-activating Protein for ARF6 That Is Involved in Actin Cytoskeleton Organization

Abstract: The ADP-ribosylation factor (ARF) 6 small GTPase regulates vesicle trafficking and cytoskeletal actin reorganization. The GTPase-activating proteins (GAPs) catalyze the formation of inactive ARF6 GDP . Centaurin-␣ 1 contains an ARF GAP and two pleckstrin homology (PH) domains, which bind the second messenger phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ). Here, we show that centaurin-␣ 1 specifically inhibits in vivo GTP loading of ARF6 and redistribution of ARF6 from the endosomal compartment to the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 16 publications
(27 reference statements)
6
78
0
1
Order By: Relevance
“…The active form of ARF6, ARF6-GTP, interacts with downstream effectors in the LHCGR signaling pathway to promote receptor internalization. In this study ARF6 activation by HCG-stimulated HLHCGR was determined using a GST-GGA3 PBD pulldown assay (23,25,52). HCG-stimulation of HLHCGR increased cellular levels of ARF6-GTP but not ARF1-GTP, while the Myr-ARF6 peptide but not Myr-ARF1 peptide inhibited HCG-stimulated ARF6 activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The active form of ARF6, ARF6-GTP, interacts with downstream effectors in the LHCGR signaling pathway to promote receptor internalization. In this study ARF6 activation by HCG-stimulated HLHCGR was determined using a GST-GGA3 PBD pulldown assay (23,25,52). HCG-stimulation of HLHCGR increased cellular levels of ARF6-GTP but not ARF1-GTP, while the Myr-ARF6 peptide but not Myr-ARF1 peptide inhibited HCG-stimulated ARF6 activation.…”
Section: Discussionmentioning
confidence: 99%
“…NM23-H1 H118C was generated by using QuickChange site-directed mutagenesis kit (Stratagene). GST-GGA3 protein binding domain (PBD) and GFP-cytohesin 2 plasmids described previously (23)(24)(25). EPS15 (EGFR pathway substrate clone 15) dominant negative (DN) mutant excised from pEGFP plasmid by EcoRI digestion and subcloned into the EcoRI site of pCMV-FLAG vector (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian cells, localized PtdIns (3, 4, 5), P3 production, and PI3K activity control polarization and migration during chemotactic movement (47). Phosphatidylinositol-3,4,5-triphosphate also provides a docking site for regulators and effectors of the small GTPase Arf6, which regulates actin remodeling (48). AKT is the other well known effector of PI3K signaling.…”
Section: Mta1 Expression Inversely Correlates With Pten Expresmentioning
confidence: 99%
“…p42 IP4 can shuttle between cytosol, nucleus and plasma membrane, depending on the cell stimulation situation . Several interaction partners of p42 IP4 have been identified, such as casein kinase I (Dubois et al 2001(Dubois et al , 2002, nucleolin , protein kinase C , several ARFs (Thacker et al 2004;Venkateswarlu et al 2004) GAKIN (Venkateswarlu et al 2005;Horiguchi et al 2006), the peptidase nardilysin (Stricker et al 2006) or F-actin (Thacker et al 2004). It has been shown that p42 IP4 is a component of the neuronal phosphatidyl inositol 3-kinase cascade and is involved in dendritic differentiation/synaptic plasticity and/or transport of PtdIns(3,4,5)P 3 -containing vesicles along axons to regulate neuronal cell polarity (Horiguchi et al 2006;Moore et al 2007).…”
mentioning
confidence: 99%